2013
DOI: 10.1093/abbs/gmt086
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-based analysis of differentially expressed proteins in the CXCR1-knockdown gastric carcinoma MKN45 cell line and its parental cell

Abstract: C-X-C chemokine receptor types 1 (CXCR1), a cell-surface G-protein-coupled receptor has been found to be associated with tumorigenesis, development, and progression of some tumors. Previously, we have found that CXCR1 overexpression is associated with late-stage gastric adenocarcinoma. We also have demonstrated that knockdown of CXCR1 could inhibit cell proliferation in vitro and in vivo. In this study, we compared the changes of protein expression profile between gastric carcinoma MKN45 cell line and CXCR1-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Western blotting was performed in accordance with a previously described protocol. 12 Cells were collected from flasks and washed 3 times with cold PBS. Tissue samples (3 glioma tissues and 1 normal brain tissue resected for the treatment of nonglioma disease) were ground with liquid nitrogen and lysed at 4°C for 30 minutes in lysis buffer (50 mM Tris, pH 7.4, 100 mM NaCl 2 , 1 mM MgCl 2 , 2.5 mM Na 3 VO 4, 1 mM phenylmethylsulfonyl fluoride, 2.5 mM EDTA, 0.5% Triton X-100, 0.5% NP-40, and 5 mg/mL each of aprotinin, pepstatin A, and leupeptin).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed in accordance with a previously described protocol. 12 Cells were collected from flasks and washed 3 times with cold PBS. Tissue samples (3 glioma tissues and 1 normal brain tissue resected for the treatment of nonglioma disease) were ground with liquid nitrogen and lysed at 4°C for 30 minutes in lysis buffer (50 mM Tris, pH 7.4, 100 mM NaCl 2 , 1 mM MgCl 2 , 2.5 mM Na 3 VO 4, 1 mM phenylmethylsulfonyl fluoride, 2.5 mM EDTA, 0.5% Triton X-100, 0.5% NP-40, and 5 mg/mL each of aprotinin, pepstatin A, and leupeptin).…”
Section: Methodsmentioning
confidence: 99%
“…The two receptors share a 78% homology (Murphy, 1994). However, differences in their N-terminal domains result in different binding specificities (Murphy, 1994;Hu et al, 2013).…”
mentioning
confidence: 99%
“…The knockdown of CXCR1 was reported to be able to prohibit the proliferation of cancer cells and even induce tumor cell apoptosis in gastric cancer. Also, the knockdown of CXCR1 could lead to the down-regulation of the phosphorylation level of serine/threonine protein kinase (AKT) and extracellular signal-regulated kinase (ERK) 1/2 [33], indicating that AKT and ERK might be involved in the downstream of CXCR1 signal pathway. Another report showed that CXCR1 could up-regulate matrix metalloproteinase-9 (MMP-9) expression by activating JNK/c-Jun and ERK/Ets-1 pathways [34, 35], thus resulting in more aggressive biological characteristics of cancer cells.…”
Section: Discussionmentioning
confidence: 99%